Functional and Logic Programming 10th International Symposium, FLOPS 2010, Sendai, Japan, April 19-21, 2010. Proceedings - Blume, Matthias.; Kobayashi, Naoki.; Vidal, Germǹ. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 10th International Symposium on Functional and Logic Programming, FLOPS 2010, held in Sendai, Japan, in April 2010. The 21 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 49 submissions. The papers are organized in topical sections on types; program analysis and transformation; foundations; logic programming; evaluation and normalization; term rewriting; and parallelism and control.